Microstructure investigation of laser additively manufactured Si/SiC ceramic - Masina Bathusile; Lekoadi Paul (MATEC Web of Conferences)
This study reports on the microstructure properties of Si/SiC ceramic produced using a laser additive manufacturing process. Several specimens of different laser energy density outputs were produced. The structural analysis revealed that the microstructure was significantly affected by the reduction of the laser energy density output whereby defects such as porosity were observed. It was found that the microstructure properties showed significant improvement at 4819 J/cm2, laser energy density output. No new phases were found due to the increased laser energy density output.